George Woodyard: The Legacy of a Scholar - KUDPS, KUDPS (Latin American Theatre Review, 2011)
George Woodyard was exceedingly modest about his achievements. In fact,he was so modest that most of us were unaware of the number and range ofhis publications and editorial activities. We decided to publish a listing of hisaccomplishments in this special issue as a way of recognizing them publiclyand also of providing bibliographical information to those scholars who shareGeorge’s passion for everything related to Latin American theatre. As faras we know, the last time that George updated his Curriculum Vitae was inJanuary 2008. We have done our best to include activities and publicationsfrom the last years of George’s remarkably productive life and apologize forany omissions.For narrative accounts of George’s life and achievements, see: Vicky Unruh,“A Virtuoso Performance: George Woodyard and Latin American Theatre,”Latin American Theatre Review 30.2 (1997): 7-16, and the “Auto-Archive”that George prepared for Theatre Journal 56.3 (2004): 547-51.